9,10-Bis(iodoethynyl)anthracene - Nehemiah Antoine; Marisa James; Keenan Dungey; Colin McMillen; Jared Pienkos (IUCrData, 2023)
The title compound, C18H8I2, is an ethynyl-substituted anthracene. The C—C—I bond angles deviate from 180°, being affected by intermolecular I...π interactions. These interactions form a two-dimensional supramolecular structure further supported by offset π–π stacking of neighboring anthracene moieties.